Defluoridation of Drinking Water by Tamarind Bark and its Leaves - SANTHI, D. (Asian Journal of Chemistry, 2010)
A simple and economic method of defluoridation of drinking water has been adopted as an adsorbent like tamarind bark and its leaves. The botanical name of tamarind is Tamarindus indica. It has the highest capacity of removing fluoride from drinking water.